Teams Games Tournament Cooperative Learning and Elementary Students’ Indonesian Language Learning Outcomes: A One-Group Pretest-Posttest Study in Kandibata Village - Chindi Clodia Br. Tarigan; Agnes Salsalina Br. Sembiring; Irmatansy Alodya Sitorus; Meikardo Samuel Prayuda (Pustaka Karya Mandiri, 2025)
Indonesian language learning in elementary school should develop students’ ability to listen, speak, read, write, understand texts, and communicate ideas meaningfully. However, teacher-centered instruction may reduce students’ motivation, participation, and understanding, especially when learning activities are dominated by explanation, reading, and memorization. This study aims to examine the improvement of elementary students’ Indonesian language learning outcomes after the implementation of the Teams Games Tournament cooperative learning model. This study employed a quantitative pre-experimental design using a one-group pretest-posttest model. The participants were 10 elementary students in Kandibata Village. The learning material focused on fictional stories in Indonesian language learning. Data were collected through pretest and posttest scores and were analyzed using descriptive statistics and paired-sample t-test. The findings show that students’ learning outcomes increased after the implementation of the Teams Games Tournament model. The mean pretest score was 57.5, while the mean posttest score increased to 86.7. The average gain was 29.2 points. The paired-sample t-test showed a significant difference between pretest and posttest scores, with t = 11.710 and p < .001. These findings indicate that Teams Games Tournament cooperative learning was associated with a substantial improvement in students’ Indonesian language learning outcomes. The study concludes that TGT can create a more active, enjoyable, competitive, and collaborative learning atmosphere, although future studies should use larger samples and control groups to strengthen causal claims.